e-LEADERSHIP: Faktor Kunci Pengembangan Kapasitas Teknologi Informasi dan Komunikasi di Daerah - Anwaruddin, Awang (Pusjar SKPP Lembaga Administrasi Negara, 2009)
Leadership is not limited to a position or job; it is a worldview and a way of being in the world. It takes vision and imagination as well as knowledge, to be a leader. We define leadership as the ability to bring people, tools and resources together to solve problems and achieve results. In the world today, we need to bring people together across national, geographic, cultural and other boundaries, using communications technologies tools to achieve results. e-Leadership means a balancing many roles and carrying them out via communications technologies. Thus, e-Leadership is no different from any other form of effective leadership except that in e-leadership you have no option but to be very good at it. It requires a high level of transformational leadership because of the highly participative nature of the e-world between e-organisations and e-customers and the interconnectedness between leader and follower with the ever-increasing reality of the blurred lines between the two (Robert Burke: 2008). Key Word: e-Leadership, e-Government, Kepemimpinan transformasional, Virtual tim, Komunikasi multilevel, Profesionalitas